Connecting with home, keeping in touch: physical and virtual mobility across stretched families in sub-Saharan Africa. (24th May 2018) - Porter, Gina; Hampshire, Kate; Abane, Albert; Munthali, Alister; Robson, Elsbeth; Tanle, Augustine; Owusu, Samuel; de Lannoy, Ariane; Bango, Andisiwe
Abstract: There is a long history of migration among low-income families in sub-Saharan Africa, in which (usually young, often male) members leave home to seek their fortune in what are perceived to be more favourable locations. While the physical and virtual mobility practices of such stretched families are often complex and contingent, maintaining contact with distantly located close kin is frequently of crucial importance for the maintenance of emotional (and possibly material) well-being, both for those who have left home and for those who remain. This article explores the ways in which these connections are being reshaped by increasing access to mobile phones in three sub-Saharan countries – Ghana, Malawi and South Africa – drawing on interdisciplinary, mixed-methods research from twenty-four sites, ranging from poor urban neighbourhoods to remote rural hamlets. Stories collected from both ends of stretched families present a world in which the connectivities now offered by the mobile phone bring a different kind of closeness and knowing, as instant sociality introduces a potential substitute for letters, cassettes and face-to-face visits, while the rapid resource mobilization opportunities identified by those still at home impose increasing pressures on migrant kin. Résumé: En Afrique subsaharienne, les familles à bas revenu ont une longue histoire de migration, avec des membres (généralement jeunes, souvent des hommes) qui s'en vont chercher fortune dans des lieux qu'ils perçoivent comme plus favorables. Les pratiques de mobilité physique et virtuelle de ces familles étirées sont souvent complexes et circonstancielles, mais le maintien du contact avec les parents éloignés est souvent d'une importance cruciale pour préserver le bien-être affectif (voire matériel) de ceux qui partent et de ceux qui restent. Cet article explore la manière dont ces liens sont modifiés par l'accès croissant au téléphone portable dans trois pays subsahariens (Ghana, Malawi et Afrique du Sud) en s'appuyant sur des recherches interdisciplinaires et multi-méthodes portant sur vingt-quatre sites allant de quartiers urbains pauvres à des hameaux ruraux reculés. Les récits recueillis à l'une et l'autre extrémité de ces familles étirées présentent un monde dans lequel les connectivités aujourd'hui rendues possibles par le téléphone portable donnent naissance à un type différent de proximité et de savoir, car la socialité instantanée peut se substituer aux lettres, aux cassettes et aux visites physiques, tandis que les opportunités de mobilisation rapide de ressources identifiées par ceux qui restent renforcent les pressions qui s'exercent sur les parents migrants.